Public Wi‐Fi provision by Australian local government authorities. Issue 4 (5th September 2019) - McShane, Ian; Grechyn, Viktor
Abstract: Investment by Australian local government authorities (LGAs) in public Wi‐Fi (PWF) provision has grown substantially in recent years. PWF represents the first significant venture of LGAs into telecommunications, a field of national jurisdiction, and thus is a precursor of wider local investment in digital communication technologies, particularly the Internet of Things and other 'smart city' infrastructure. However, there has been little published analysis of PWF provision and use in Australia. This knowledge gap limits understanding of the rationales, business models, and uses and impact of investment in these networks and offers little guidance for local authorities and communities contemplating wider ventures in the field of digital networks. This article draws on a national survey of PWF provision by LGAs, together with interview data and critical analysis of policy and institutional settings, to present an overview of local PWF provision in Australia. The analysis highlights some familiar problems associated with LGA infrastructure investment and service delivery, as well as some novel challenges posed for local managers by digital communication networks. Following an empirical mapping of PWF provision in Australia, we explore three significant themes that our research in this field highlights: accountability and transparency, competence in the field of information and communication technologies (ICT) and evaluation. Abstract : Around two‐thirds of Australian local government authorities provide free public Wi‐Fi. This article presents the first national‐level analysis of this service, and identifies some issues relating to local government investment in digital communication networks.